In vitro enzyme mediated synthesis of metal sulfide nanoparticles: control of particle size of CdS, Ni7S6, PbS, Co3S4 nanoparticles using synthetic peptides - Ansary, Abu Ayoobul; Khan, Muhammed I.; Gaikwad, Sushama M. (Science of Advanced Materials, 2012)
We report the use of enzyme sulfite reductase for the in vitro synthesis of technologically important metal sulfide quantum dots viz. Co3S4, PbS and Ni7S6. Also we report the use of synthetic peptides to control the particle size of the above metal sulfide quantum dots in addition to CdS, synthesized using enzyme. Sulfite reductase when incubated with aqueous CdCl2, or Co(NO3)(3) or NiCl2 or Pb(NO3)(2), and Na2SO3 in the presence of the appropriate capping peptide resulted in the synthesis of particle size controlled CdS, Co3S4, Ni7S6, or PbS quantum dots respectively. These, enzyme mediated synthesized and size controlled metal sulfide quantum dots, were characterized using Absorbance and photoluminescence spectrometry, X-ray diffraction, X-ray photoelectron spectroscopy and High resolution-transmission electron microscopy.
Keywords: Capping Peptide; Enzyme; Metal Sulfide Nanoparticles; quantum dots; Size Control; Sulfite Reductase

Biomimetic synthesis of CdSe nanoparticles with potential bioimaging applications - Ansary, Abu Ayoobul; Uddin, Imran; Khan, Muhammed I. (International Journal of Pharmaceutical Sciences and Research, 2017)
This study presents in vitro biomimetic synthesis of CdSe nanoparticles using the enzyme, NADPH dependent-Nitrate reductase purified from fungus, Fusarium oxysporum. The synthesis of CdSe nanoparticles was accomplished in the presence of a synthetic peptide having amino acid sequence (γ-Glu-Cys-Glu-Cys)-Gly, which acted as binding molecule. The nanoparticles were synthesized in the size range of 3.9–9.0 nm was analysed using TEM. Further characterization of nanoparticles was done using techniques such as UV, PL, XPS, and FTIR. The as-synthesized CdSe nanoparticles were water dispersible containing free reactive amino groups. These CdSe nanoparticles were conjugated with bi-antennary and tri-antennary glycopeptides opening up the possibilities for their applications in bioimaging. These significant observations will help better understand the mechanism of biosynthesis of fluorescent nanoparticles using fungi. These findings promise an alternative strategy for an eco-friendly, economical, and large-scale synthesis of water dispersible CdSe nanoparticles. These CdSe nanoparticles have promising biomedical-imaging applications without a need for further functionalization.